If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -9 + 3x = -14 Reorder the terms: -9 + x + 3x = -14 Combine like terms: x + 3x = 4x -9 + 4x = -14 Solving -9 + 4x = -14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 4x = -14 + 9 Combine like terms: -9 + 9 = 0 0 + 4x = -14 + 9 4x = -14 + 9 Combine like terms: -14 + 9 = -5 4x = -5 Divide each side by '4'. x = -1.25 Simplifying x = -1.25
| 1=2u+7 | | -5(2x+-10)=-35x+50+25x | | 1=7+2 | | 7.50+1m=2.50m | | y^3-4y^2+3y=o | | 14x-(-3)=5 | | 5(2n+3)-5=-70 | | 17x*6x-4*3=10 | | 0=x^2-10x+24 | | 5(40x-260)-25(80-20x)=226 | | 13-5x+7x-19=37 | | -8n+2n=-8-7n | | 25+.10x=35+.5x | | -1(3x+-13)=37 | | 0=5(7-x)+12 | | k-8=4 | | 5x+8=7c-0 | | 1.5-(32.8)= | | 7x-3.2=5.7 | | 4-d=(-d-4) | | 9(x+4)=-5x+4 | | 5x-8+3x=18 | | 6=c-9 | | -6(1+2x)=6(2x+1)+2x | | 60-5x=135-10x | | 43m+10-26m=27 | | 4y+3=(3-y)2 | | 32+-4x=84 | | 2d+1=16-d | | -48+6x=60+10x | | 0=x^4-10x^2+24 | | a=16+a |